A comprehensive framework identifying barriers to global health R&D innovation and access - Ming Ong (BMJ Global Health)
Advancements in research and development (R&D) have the potential to address pressing global health challenges. However, numerous barriers hinder innovation and access, particularly in areas of market failure, and there is an absence of a cohesive consensus on defining these various impediments. This paper presents a framework identifying the barriers that impede global health innovation and hinder equitable access to health technologies.The framework presents clear typologies of barriers across global health R&D thematic areas. These include the market failures that require R&D incentives to stimulate innovation, how the complexity of product registration hinders access within specific regulatory domains and how health system implementation issues prevent affected populations from accessing the tools they require. Current and historical examples are provided for each end-point, and three case studies explore key barriers and how solutions have or may be applied.This analysis contributes by adding to the body of knowledge on global health R&D and provides an analysis tool to policy-makers, researchers and stakeholders involved in addressing the barriers and promoting equitable access to healthcare innovations. The framework serves as a practical tool to guide future research, policy development and implementation efforts towards achieving sustainable global health outcomes.